Growing with wheat and barley rusts for three decades - BHARDWAJ, S.C. (Indian Phytopathology, 2017)
I feel honoured and elated for being conferred S.N. Dasgupta memorial award. I am grateful to the Indian Phytopathological Society to bestow this honour upon me which is named after one of the great Scientists of all the times. Dr. Dasgupta belonged to a family of distinguished people. He did pioneer research on physiological plant pathology, was an excellent Fungal taxonomist who rose to become the Vice Chancellor of Kalyani University, a position he served for two terms. I think he would have been very happy today to see that I would be discussing very important disease rust and sharing my experience with this august gathering, on ways and means to secure wheat. This crop is synonym to economic health and nutritional security of many countries with India no exception. Today we remember Dr. Dasgupta for the work done by him for the progress of biosciences and this lecture is a tribute to the great soul.